Characterization of a new IN-I-PpoI fusion protein and a homology-arm containing transgene cassette that improve transgene expression persistence and 28S rRNA gene-targeted insertion of lentiviral vectors. - Alisa Nousiainen; Diana Schenkwein; Seppo Ylä-Herttuala (PLoS ONE, 2023)
Targeting transgene integration into a safe genomic locus would be very important for gene therapy. We have generated lentivirus vectors containing the ribosomal RNA-recognising I-PpoI endonuclease fused to viral integrase, and transgene cassettes with target site homology arms to enhance insertion targeting. These new vectors were characterised with respect to the persistence of transgene expression, insertion targeting efficiency and chromosomal integrity of the transduced cells. The aim was to find an optimally safe and effective vector for human gene therapy. Fusion protein vectors with high endonuclease activity were the most effective in the accurate targeting of transgene insertion. The homology construct increased the insertion targeting efficiency to 28% in MRC-5 cells. However, karyotyping analysis showed that the high endonuclease activity induced the formation of derivative chromosomes in as many as 24% of the analysed primary T lymphocytes. The persistence of transgene expression was excellent in homology arm-containing fusion protein vectors with reduced endonuclease activity, and these fusion proteins did not cause any detectable chromosomal rearrangements attributable to the endonuclease activity. We thus conclude that instead of the fusion protein vectors that carry a highly active endonuclease, our vectors with the ability to tether the lentivirus preintegration complex to benign loci in the genome without high ribosomal DNA cleavage activity are better suited for lentivirus-based gene therapy applications.